Stories of values. Value of stories. An alliance of ethics, literature and medical humanities - Cattorini, Paolo Marino (Medicina Historica, 2017)
In order to rethink the scopes, methodology and teaching criteria of healthcare professions, we have to take some theoretical steps: exploring the phenomenology of illness, recognizing the narrative dimension of medical enterprise and of clinical ethics, opening a fruitful dialogue with art criticism, underlining the mutual duties of the therapeutic covenant, and considering the cinema as a test bench for the medical humanities (history of medicine included). The inner weaving between facts and values, biological data and shared decisions in the sphere of the healing endeavour finds its roots in the ancient importance assigned, since the Greek thought, to the relationship between cases and theories, story-telling and conceptual reasoning.